Sirkulasi Historis Pasang-Surut Tiga Kerajaan Besar Islam di Abad Pertengahan - Ma'rifah, Rifa Tsamrotul; Syihabuddin, Muhammad; Aulia, Nur Annisa; Nisa, Fitri Dwi Zuhrotun (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2024)
The discourse on the treasures of Islamic civilization must be studied more deeply. This is because the study never ceases to be discussed. This paper aims to understand the cycle of a great medieval empire, both its progress and decline. The method used is a literature study or library research related to historical or other similar themes. Based on the theory of the History of Islamic Civilization. For data collection by analyzing historical texts, collecting relevant data, and describing. The results of this paper reveal that: First, every kingdom will experience glory and decline because a civilization cannot be separated from it. Second, the three empires in question are the Ottoman Turkish Empire, Safawi Persia, and Mughal India. All three experienced a process of ups and downs in their civilization. Third, the factors that caused the triumph of the three dynasties can be seen from various cultural aspects, and the factors that caused the collapse of the three dynasties had many similarities in the weak leadership of the last sultan.Â Â